Assessing the Therapeutic and Toxicological Profile of Novel Acetylcholinesterase Reactivators: Value of In Silico And In Vitro Data - Ramalho, Teodorico C; de Castro, Alexandre A; Leal, Daniel H S; Teixeira, Jessika P; da Cunha, Elaine F F; Kuca, Kamil (Current medicinal chemistry, 2023)
Organophosphorus compounds (OP) make up an important class of inhibitors, mostly employed as pesticides, even as chemical weapons. These toxic substances act through the inhibition of the acetylcholinesterase (AChE) enzyme, which results in elevated synaptic acetylcholine (ACh) levels, leading to serious adverse effects under the cholinergic syndrome. Many reactivators have been developed to combat the toxic effects of these AChE inhibitors. In this line, the oximes highlight because of their good reactivating power of cholinesterase enzymes. To date, no universal antidotes can reactivate AChE inhibited by any OP agent. This review summarizes the intoxication process by neurotoxic OP agents, along with the development of reactivators capable of reversing their effects, approaching aspects like the therapeutic and toxicological profile of these antidotes. Computational methods and conscious in vitro studies, capable of significantly predicting the toxicological profile of these drug candidates, might support the process of development of these reactivators before entering in vivo studies in animals, and then clinical trials. These approaches can assist in the design of safer and more effective molecules, reducing related cost and time for the process.
Keywords: acetylcholinesterasa; organofosforové sloučeniny; reaktivátory cholinesterasy; zvířata; Oximes; cholinesterasové inhibitory; Antidotes; Acetylcholinesterase; Cholinesterase Inhibitors; Animals; oximy; antidota; Cholinesterase Reactivators; Organophosphorus Compounds